2011
DOI: 10.1016/j.colsurfa.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of dolomite as foaming agent and its effect on the microstructure of aluminium metal foams—Comparison to titanium hydride

Abstract: Abstract:In this paper dolomite MgCa(CO 3 ) 2 a naturally occurring mineral was demonstrated to be an effective foaming and stabilizing agent for aluminium with several notable advantages relative to the currently used titanium hydride foaming agent. Characteristic cell structures and microstructural features of foams produced with a dolomite foaming agent are examined and the properties of dolomite based foams produced in a one step process are compared with those produced using titanium hydride based process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…This fact is not surprising considering that, for a given melt viscosity, the amount of gas that can be efficiently retained and properly dispersed during foaming is usually the same. More gas released also increases the probability that the gas bubbles will coalesce and create a less uniform porous structure [29], a fact clearly observed in Figure 7b for Al–10Ni foams with 10 wt.% dolomite. These findings are in agreement with the study conducted by Barnhart et al [17,54], in which it was demonstrated that there is an optimal content of foaming agent above which the maximum expansion of the foams becomes independent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This fact is not surprising considering that, for a given melt viscosity, the amount of gas that can be efficiently retained and properly dispersed during foaming is usually the same. More gas released also increases the probability that the gas bubbles will coalesce and create a less uniform porous structure [29], a fact clearly observed in Figure 7b for Al–10Ni foams with 10 wt.% dolomite. These findings are in agreement with the study conducted by Barnhart et al [17,54], in which it was demonstrated that there is an optimal content of foaming agent above which the maximum expansion of the foams becomes independent.…”
Section: Resultsmentioning
confidence: 99%
“…A potential blowing agent for aluminum foam production that is both safer and inexpensive is dolomite. In addition to the attractive price ($20–30/ton) and abundance, dolomite, which is a double carbonate of calcium and magnesium (CaMg(CO 3 ) 2 ), can act simultaneously as a foaming agent and as a foam stabilizer [29]. It can act as a foaming agent owing to the release of CO 2 gas over a wide temperature range (600–800 °C), and as a stabilizer due to the oxides formed in situ (MgO, CaO) and/or undecomposed CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, aluminum foam produced using carbonates has a finer cell structure than that produced using TiH 2 . The effect of oxide layer on foam stabilization has been reported from other researchers [3][4][5]. On the other hand, foam by TiH 2 are stabilized by solid particles, like SiO 2 [6].…”
Section: Introductionmentioning
confidence: 86%